Reframing History Education through Local Wisdom: Pedagogical Integration of Cultural Traditions to Foster Historical Consciousness in an Indonesian Madrasah - Mu'arifah Mu'arifah; Warto Warto; Djono Djono (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
Integrating local wisdom into history education has increasingly been recognized as an important approach to contextualizing historical learning and connecting historical knowledge with students’ cultural experiences. However, existing studies often position local traditions merely as supplementary learning materials rather than examining how they can be pedagogically integrated to foster students’ historical understanding. This study investigates how local wisdom can be integrated pedagogically into history learning and how such integration contributes to the development of students’ historical consciousness. The research employed a qualitative case study conducted at MA Sultan Agung Sukolilo, Pati Regency, Indonesia. Participants included 36 tenth-grade students, a history teacher, the school principal, and the head of the Sultan Agung Foundation. Data were collected through classroom observations, in-depth interviews, and document analysis, and were analyzed using thematic analysis informed by Rusen’s framework of historical consciousness. The findings reveal that the Meron tradition functions as a pedagogical medium that enables students to engage with cultural practices, interpret their historical meanings, and reflect on their relevance to contemporary social life. Through this process, students begin to understand local traditions as part of their community’s historical experiences. The analysis indicates that students’ historical consciousness develops primarily at the levels of traditional and exemplary historical consciousness, where traditions are perceived as cultural heritage and sources of moral values. This study proposes a pedagogical framework of local wisdom integration involving cultural exploration, historical interpretation, and reflective engagement with local traditions. The findings highlight the potential of local cultural practices as pedagogical resources for developing culturally responsive and contextually grounded history education.